Pre-school Teachers' Stereotypes and Self-Efficacy are Linked to Perceptions of Behavior Problems in Newly Arrived Refugee Children - Chwastek, Sandy; Leyendecker, Birgit; Heithausen, Anna; Ballero Reque, Cristina; Busch, Julian (Frontiers in Psychiatry, 2021)
Introduction: Since 2015, increased numbers of refugee families with pre-school-aged children have arrived in Germany. In pre-schools, teachers' professional competence for teaching those children and adapting to their socio-emotional needs has become increasingly important. Previous research linked teachers' stereotypes and cultural beliefs to their self-efficacy and enthusiasm when teaching immigrant children. This study investigated the links between domains of pre-school teachers' professional competence (i.e., negative stereotypes, multicultural beliefs, self-efficacy, and enthusiasm when teaching newly arrived refugee children), and examined whether teachers' professional competence was linked to their perceptions of newly arrived refugee children's behavior problems. Method: In a cross-sectional self-report survey, N = 147 German pre-school teachers reported on their professional competence and completed the Strengths and Difficulties Questionnaire (SDQ) for a selected refugee child from their pre-school group. We used regression modeling to link teachers' negative stereotypes and multicultural beliefs to their self-efficacy and enthusiasm for teaching refugee children. Next, we examined the links between teachers' beliefs, values, and motivational orientations to their ratings on the SDQ subscales. Last, we linked demographic data on teachers and children to teachers' professional competence and SDQ ratings. Results: Teachers with more negative stereotypes toward newly arrived refugee children and less agreement with multicultural beliefs reported lower self-efficacy and enthusiasm for teaching newly arrived refugee children. Teachers with more negative stereotypes perceived more hyperactivity/inattention and total difficulties. Teachers with higher self-efficacy perceived less hyperactivity/inattention, less total difficulties, and more prosocial behavior. Additionally, teachers who had more experience with refugee children reported more negative stereotypes and higher agreement with multicultural beliefs. Teachers having more overall work experience perceived more total difficulties. Boys were perceived to display more externalizing behavior problems, less prosocial behavior, and more total difficulties. Older children were perceived as displaying more prosocial behavior and children from African countries were perceived as displaying more conduct problems. Discussion: Our findings suggest that pre-school teachers' stereotypes and self-efficacy might be related to perception biases concerning newly arrived refugee children's externalizing behavior problems. Implications for the professional development of pre-school teachers and teacher-informant diagnostics of refugee children's socio-emotional needs are discussed.